Pengaruh Pemberian Ekstrak Biji Luffa acutangula, Roxb pada Mencit Betina Galur Swiss Webster terhadap Lama Siklus Estrus dan Jumlah Folikel Muda - Purwaningsih, Endang (Jurnal Kedokteran YARSI, 2008)
The purpose of thepresent study was to investigate the effect of oral Luffa acutangula, Roxb seed extract respectively in the estrous cycle period and the total number of immature follicles on female mice, Swiss Webster strain. In this study, experimental animals weredivided to 5 treatment groups. The first 3 mice of each group were treated with 200, 300 and 400 mg/kg body weight of seed extract orally. The remaining 2 mice served as treated control (given aquabidest only) and samecontrol. Treatment wih seed extract of each group was given everyday for 20 and 40 days. All female mice whichwere treated with various doses (200, 300 and 400 mg/kg body weight) of Luffa acutangula, Roxb seed extract showed the highly significant different in the estrous cycle period and the number of immature follicles compared to control groups on day 20 and 40. The duration of estrous cycle of the treatment group was longer and the number of immature follicles were decreased; and the duration cycle was longer significant for the 40 day.